AETIOLOGY OF TRICUSPID REGURGITATION - Ahmad, Rehan; Nawaz, Haq; Nazar, Hassan Shahzad; Ahmad, Sarfraz; Rabbani, Aftab; Ahmed, Basharat (Journal of Ayub Medical College Abbottabad, 2011)
Background: Tricuspid regurgitation (TR) is regarded as a secondary disorder. Aim of the study was to know what percentage is secondary to heart and lung disease and its prevalence in normal adults. Methods: Two hundred and 30 adults with clinically detectable TR were studied clinically to know the cause of TR. Results: Thirteen percent of the adults were normal without any detectable cause for TR. In others, 24% of TR cases were secondary to ischemic heart disease (IHD) and hypertension was found in 14% cases. Sixteen percent had rheumatic heart disease (RHD) while chronic obstructive lung disease was found in 23% cases. The rest of 10% cases of TR had cardiomyopathy (CMP) and congenital heart disease as secondary causes. Conclusion: Ischemic heart disease, COPD and hypertension are common causes of TR. Others include RHD, CMP and congenital heart disease. Thirteen percent of apparently normal adults had TR. Keywords: Tricuspid regurgitation, IHD, Hypertension, COPD